Implementation of Character Values In The Thematic Learning Contained In Social Sciences In Ibtidaiyah Al Iman Merden Padureso Madrasah - Rini, Diana Dwi Puspita (Universitas Negeri Padang, 2022)
This study aims to describe: 1) the implementation of character values , 2) barriers to implementing character values , and 3) solutions to overcome obstacles in implementing character education. This research is a qualitative descriptive study. Data collection techniques using observation, interviews, and documentation. Data analysis used steps of data collection, data reduction, data presentation, and drawing conclusions. The results showed that (1) the implementation of character values was carried out to foster social character, mutual respect and respect for students' opinions, interact and help each other, ask questions, explore students' knowledge and experiences, form an attitude of trust with their own abilities, and form a cooperative attitude. in groups, study hard, be polite and courteous. (2) Barriers to the implementation of character values are that there are some students who do not like learning, do not pay attention to the teacher's explanations, have difficulty in memorizing the material, and do not yet understand the character values applied in learning. (3) Solutions to overcome obstacles are carried out by teachers in collaboration with other teachers to provide guidance to students, principals and teachers also provide examples, remind students who commit violations, remind students to obey school rules, enter class on time and pay attention to the material explained. by the teacher.Keywords: Implementation, Social Studies, Character, Values, Thematic